Variation in deliberate self-harm around Christmas and New Year. - Bergen, H; Hawton, K (2007)
Seasonal and temporal variations in suicide by patient and demographic groups, though important, have been investigated infrequently. This study examined patterns of non-fatal deliberate self-harm (DSH) during Christmas and New Year (from December 16th to January 6th) by specific patient and demographic group. The sample comprised 19,346 people who presented with 31,369 episodes of DSH to a general hospital Emergency Department in Oxford, UK. Autoregression analysis of all episodes from 1976 to 2003 (controlling for day of the week, month and year) revealed significant reductions (-30% to -40%) in the occurrence of DSH compared with expected numbers on each day from December 19th to 26th (except the 23rd), though no significant increase was found on any of the subsequent 11 days. When analysed separately, young people aged under 25 years showed decreases (-60%) in the occurrence of DSH on several days throughout Christmas (p<0.001) and New Year (p<0.01). Patients with partner relationship problems showed a decrease 3 days before Christmas Day (-80%, p<0.001) and an increase on New Year's Day (+100%, p<0.01). Patients with family relationship problems showed decreases before Christmas and after New Year (-60%, p<0.01). Patients with social isolation problems, or a previous history of DSH showed decreases (-60%, p<0.01) before Christmas only. Patients who used alcohol at the time of DSH or in the 6h beforehand, but did not chronically misuse alcohol, showed an increase (+250%, p<0.01) on New Year's Day. There was no significant variation in the occurrence of DSH for patient groups with either low/medium or high suicide intent. The findings elucidate how social and individual factors may interact in contributing to DSH. They are of theoretical interest, and have important clinical implications regarding identification of patient groups especially susceptible to DSH at New Year.